Value-Added Products for Fresh Highbush Blueberries - Ruiqi Li; Liwei Gu (EDIS)
Blueberries are one of the most popular fruits worldwide. Blueberries’ health benefits have fueled this popularity, and today, blueberries can be found in products ranging from nutritional supplements to pet food. This 4-page fact sheet covers the processing methods such as freezing or drying that transform fresh blueberries into ingredients that can be used in other products. Written by Ruiqi Li and Liwei Gu, and published by the UF Food Science and Human Nutrition Department, June 2015.